Multiparametric ultrasound findings in a patient with polyorchidism. (August 2017) - Rafailidis, Vasileios; Arvaniti, Mary; Rafailidis, Dimitrios; Sfoungaris, Dimitrios
Polyorchidism is a rare condition usually incidentally discovered in young patients investigated with ultrasound for unrelated reasons. It is characterized by the presence of unilateral or, rarely, bilateral supernumerary testes which, depending on the type of polyorchidism, may have their own epididymis and vas deferens. Ultrasound, including B-mode and color Doppler technique, represents the primary imaging modality for the evaluation of scrotal diseases, including the characterization of supernumerary testes, which normally appear identical to the ipsilateral testicular parenchyma on every ultrasonographic technique performed. The role of MRI is thus limited to confirming ultrasonographic findings and excluding the presence of malignancy. Contrast-enhanced ultrasound is a recently introduced ultrasonographic technique providing detailed and sensitive visualization of the perfusion pattern of structures. It can thus be added to the conventional ultrasonographic examination in order to establish the diagnosis, negating the use of more expensive and time-consuming imaging modalities. We present a young patient with an incidentally found supernumerary testis, where new distinctive ultrasonographic findings, like the identification of transmediastinal vessels and a cystic appendage along with the perfusion pattern on contrast-enhanced ultrasound, established the diagnosis of polyorchidism.